2019
DOI: 10.1155/2019/6146942
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Fat Extract on UVB-Induced Photoaging In Vitro and In Vivo

Abstract: Background. Nanofat can protect against ultraviolet B- (UVB-) induced damage in nude mice. Fat extract (FE) is a cell-free fraction isolated from nanofat that is enriched with a variety of growth factors. Objective. To determine whether FE can protect against UVB-induced photoaging in cultured dermal fibroblasts and in nude mice. Method. For the in vitro study, human dermal skin fibroblasts were pretreated with FE 24 h prior to UVB irradiation. Generation of reactive oxygen species (ROS) was analyzed immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
7
35
0
Order By: Relevance
“…It has also been reported that the reductions in capillary diameter and volume are associated with vascular endothelial cell apoptosis via increased oxidative stress [26]. Furthermore, in UV-induced skin, the dermal thickness increased while the capillary density decreased, as recently reported by Deng et al [27]. We also found an inverse correlation between wrinkling and the levels of ROS and between wrinkling and the capillary number in the skin of mice ( Figure 6).…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that the reductions in capillary diameter and volume are associated with vascular endothelial cell apoptosis via increased oxidative stress [26]. Furthermore, in UV-induced skin, the dermal thickness increased while the capillary density decreased, as recently reported by Deng et al [27]. We also found an inverse correlation between wrinkling and the levels of ROS and between wrinkling and the capillary number in the skin of mice ( Figure 6).…”
Section: Discussionsupporting
confidence: 88%
“…Topical application of ATSC-Ex accelerates wound healing in vivo 2. ATE promotes HDF proliferation and migration and ECM protein production [ 64 ] Mingwu Deng Dermal fibroblasts were cultured with different concentrations of FE and then were exposed to UVB light Female BALB/c nude mice skin photoaging model 1. FE increases cell proliferation and abrogates UVB irradiation-induced cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study revealed that AST could prevent capillary regression in atrophied soleus muscles by upregulating vascular endothelial growth factor (VEGF) protein and downregulating thrombospondin-1 (TSP-1) protein in the soleus muscle of rats [45]. It has also been reported that reductions in the capillary diameter and volume are associated with vascular endothelial cell apoptosis via increased oxidative stress in hind limb unweighting of a rat model [46]. The data from the present study also indicate that the number of capillaries is markedly reduced after exposure to UV, whereas oral administration with AST prevented the decrease in capillaries in the skin of mice (Figure 4).…”
Section: Discussionmentioning
confidence: 99%